Considerations on Chanta and Politics in Argentinian Cinema of the 1960s - Rodríguez Riva, Lucía (2026)
Introduction: This paper explores the dimensions that chanta representation in Argentine political and social cinema achieves during the 1960s. Objective: To study the transformations that this stereotype —rooted in the Argentinian cultural imaginary typical of popular cinema— undergoes in films of political criticism and intervention during the 1960s.  Methods: An analysis of mise-en-scène, framing in film history, and contextualization with social and cultural series was conducted. Results: At first, the use of the chanta is observed as a reference for a decaying social system, while, in a second moment, it is linked directly to politics (in a strict, institutional sense) and appears associated with corruption, as an explanation of social disintegration. Conclusions: Being a character strongly rooted in popular imagination, the chanta is adopted by filmmakers with very diverse visions, in order to question hegemonic models.